Increasing destination loyalty of international students towards Malaysian higher educational institutions - Ai Chin Thoo; Matthew Boon Pin Lim; Hon Tat Huam; Zuraidah Sulaiman (International Journal of Evaluation and Research in Education (IJERE), 2022)
Educational tourism has gained popularity worldwide due to the emergence of the knowledge economy that has increased the global demand for tertiary education. Therefore, the trend has inspired this study to examine the factors affecting international students’ destination loyalty to revisit and recommend Malaysian higher educational institutions as their educational tourism attractions. In this study, 200 international students who were currently studying in Malaysian higher educational institutions were recruited through purposive sampling technique. The statistical package for the social sciences (SPSS) and SmartPLS were performed for data collection analysis. The findings demonstrated that the service quality, destination image, and cost of the study were positively correlated with the students’ satisfaction wherein students’ satisfaction contributed positively and significantly to the destination loyalty of international students in recommending and revisiting Malaysia for educational tourism. This study provided all the higher educational institutions and authorities in Malaysia with a better understanding of international students’ expectations and perceptions towards studying in Malaysia. Subsequently, the relevant stakeholders could implement effective strategies to improve and assist the Malaysian government in accomplishing the aspiration of becoming one of the most excellent international education hubs in the world.